Visual Semiotics of Mural Art in Yogyakarta: Negotiating Cultural Identity in Urban Spaces - Nazaruddin, M. Arief; Mahfudzi, Aan (Indonesian Scientific Publication, 2024)
This research investigates how local identity is represented in mural artworks created by urban communities in Yogyakarta, Indonesia. Using a qualitative case study methodology, the study examines murals from three locations Kampung Code, Jl. Tirtodipuran, and Sayidan employing visual semiotics and thematic analysis. Findings reveal that these murals utilize traditional symbols such as wayang, batik patterns, and agrarian motifs to assert cultural continuity and communal values. The murals in Kampung Code emphasize resistance through traditional iconography, while those in Jl. Tirtodipuran depict everyday rural life, reinforcing social bonds. In Sayidan, a hybrid aesthetic emerges as young artists integrate traditional elements with contemporary street art, expressing fluid and pluralistic urban identities. The research illustrates that murals in Yogyakarta are not merely decorative but serve as powerful mediums for cultural negotiation, identity formation, and community engagement. Through public art, communities assert their presence and preserve their heritage in the face of urban change. The study contributes to interdisciplinary discussions in urban studies, visual culture, and cultural geography by offering empirical evidence on how community-based murals articulate identity, resist gentrification, and sustain cultural heritage in Yogyakarta’s evolving urban landscape.